Diagnóstico ambiental de la quebrada San Francisco, cantón Quero, provincia de Tungurahua. - Aillón Torres, Brando Ariel (2023)
The purpose of this research is to carry out an environmental diagnosis of the San Francisco stream, located in the canton of Quero, province of Tungurahua, considering it as a fundamental tool to understand and capture the reality of the study area. This study area includes the community of Chocalo San Francisco and Cruz de Mayo, which belong to the parish of Rumipamba with approximately 185 families, Different methodologies were applied to diagnose the current state of the stream, its biophysical and socioeconomic components, and to analyse the threats, vulnerabilities and existing risks of the stream, through bibliographical, descriptive and field research, using different techniques such as the collection of water samples, laboratory analysis, tours of the area, surveys and the processing of geographical information. The results show that the study area has common characteristics of the mountains, its water supply comes from the Igualata moor and presents a very high risk of contamination, taking into account that in the upper and middle part the water quality is high and in the lower part it has a regular quality according to the Brown water quality index, another important threat is the heavy rains that in the area has already brought serious problems such as the destruction of roads which has caused deaths of people and animals. The surveys carried out in both communities included questions on basic services, rubbish collection services, type of housing, hygiene, food and nutrition, emergency information, road classification, and risks exposed in the home, The most influential results are the lack of a sewage system and the lack of a rubbish collection programme, which causes the increase and transmission of diseases associated with hygiene, as well as a high level of environmental contamination due to the burning (incineration) of rubbish and the emission of inorganic waste into the stream. In addition, the San Francisco stream has a medium risk for almost all of the hazards analysed in the methodological guide proposed by the UNDP. The majority of the population studied has no knowledge of the risks, hazards or how to act in the face of such events. Through this research we have helped the two communities of Chocalo San Francisco and Cruz de Mayo to identify the current state, possible risks and threats facing the stream.